2018
DOI: 10.1186/s13287-017-0762-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1-mediated regulation of miR-193a expression promotes the migration and proliferation of c-kit-positive mouse cardiac stem cells

Abstract: BackgroundC-kit-positive cardiac stem cells (CSCs) have been shown to be a promising candidate treatment for myocardial infarction and heart failure. Insulin-like growth factor (IGF)-1 is an anabolic growth hormone that regulates cellular proliferation, differentiation, senescence, and death in various tissues. Although IGF-1 promotes the migration and proliferation of c-kit-positive mouse CSCs, the underlying mechanism remains unclear.MethodsCells were isolated from adult mouse hearts, and c-kit-positive CSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…We also demonstrated increased c-kit expression ( Fig. 5D), corroborating previous data from Sun and coworkers [46], which demonstrated that IGF-1-mediated activation of the PI3K/AKT pathway enhanced in vitro CSC migration and proliferation by upregulating c-kit expression.…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrated increased c-kit expression ( Fig. 5D), corroborating previous data from Sun and coworkers [46], which demonstrated that IGF-1-mediated activation of the PI3K/AKT pathway enhanced in vitro CSC migration and proliferation by upregulating c-kit expression.…”
Section: Discussionsupporting
confidence: 91%
“…In the context of heart development, miRNAs with peaks at days 8, 12 and 16 seem especially relevant. MiR-126-3p, peaking at day eight, was identified as a potential biomarker for coronary artery disease [55], while miR193a-5p with a peak at day 12 was shown to repress proliferation and migration of cardiac stem cells (CSCs) through the downregulation of c-kit [56]. Peaks at day 16 were detected for members of the let-7 family that have been linked to the regulation of multiple processes, including heart development and cardiac differentiation, as well as cardiovascular diseases [52].…”
Section: Discussionmentioning
confidence: 99%
“…Saheera S et al found that oxidative stress and senescence of CSCs were alleviated after treatment with metoprolol, which increased the migration and proliferation of CSCs and was beneficial in delaying progressive cardiac remodeling [148]. Insulin-like growth factor-1 is a synthetic growth hormone that regulates cell proliferation, differentiation, senescence and death; Sun Y et al found that IGF-1 promotes the proliferation and migration of CSCs by activating the PI3K/AKT/DNMT signaling pathway [149].…”
Section: Cscsmentioning
confidence: 99%
“…Insulin-like growth factor-1 is a synthetic growth hormone that regulates cell proliferation, differentiation, senescence and death; Sun Y et al . found that IGF-1 promotes the proliferation and migration of CSCs by activating the PI3K/AKT/DNMT signaling pathway [ 149 ].…”
Section: Cellular Senescence Affects Cardiac Regeneration and Repairmentioning
confidence: 99%